Solvent extraction of light rare earths from acidic medium by Di-(2-ethylhexyl) phosphoric acid in kerosene - Khaironie Mohamed Takip,; Masturah Markom,; Meor Yusoff Meor Sulaiman, (Fakulti Kejuruteraan ,UKM,Bangi., 2015)
An organophosphorus reactant, D2EHPA, in kerosene has been employed as an extractant for solvent extraction of a mixture of light rare earths (La(III), Nd(III) and Ce(IV)) from acidic nitrate and sulphuric medium. Effect of various concentrations of acidic solutions and extractant on the extraction of rare earths was investigated. The experiments were carried out under various concentrations of aqueous phase of acidic solutions (0.1-0.5 M) and organic phase of D2EHPA (0.1-1 M) at organic-to-aqueous (O/A) phase ratio of 1. The effect of temperature on extraction was also studied by varying temperature range from 278 to 318 K. Extraction equilibrium time was investigated to determine the optimum time for extracting the studied rare earths. It was found that the extraction of 99.4%, 99.7% and almost 100% for La(III), Nd(III) and Ce(IV), respectively, was achieved from 0.1 M HNO3 feed solution with 1 M D2EHPA at room temperature. The process showed that the selective extraction was in order of La(III)<Nd(III)<Ce(IV). The loaded organic was stripped with various concentration of several acidic solutions (HCl, HNO3 and H2SO4) at O/A phase ratio of 1. It was found that the recoveries of La(III) and Nd(III) to the strip liquor were relatively moderate (45.2-67.7%), whereas losses of Ce(IV) were very low (<1.5%).